A research update on the antitumor effects of active components of Chinese medicine ChanSu - Jia, Jinhao; Li, Jie; Zheng, Qiusheng; Li, Defang (Frontiers in Oncology, 2022)
Clinical data show that the incidence and mortality rates of cancer are rising continuously, and cancer has become an ongoing public health challenge worldwide. Excitingly, the extensive clinical application of traditional Chinese medicine may suggest a new direction to combat cancer, and the therapeutic effects of active ingredients from Chinese herbal medicine on cancer are now being widely studied in the medical community. As a traditional anticancer Chinese medicine, ChanSu has been clinically applied since the 1980s and has achieved excellent antitumor efficacy. Meanwhile, the ChanSu active components (e.g., telocinobufagin, bufotalin, bufalin, cinobufotalin, and cinobufagin) exert great antitumor activity in many cancers, such as breast cancer, colorectal cancer, hepatocellular carcinoma and esophageal squamous cell carcinoma. Many pharmaceutical scientists have investigated the anticancer mechanisms of ChanSu or the ChanSu active components and obtained certain research progress. This article reviews the research progress and antitumor mechanisms of ChanSu active components and proposes that multiple active components of ChanSu may be potential anticancer drugs.